2009
DOI: 10.3233/wor-2009-0887
|View full text |Cite
|
Sign up to set email alerts
|

Moving from full-time healing work to paid employment: Challenges and celebrations

Abstract: Background: The experiences and barriers associated with the return to paid employment following healing from recurrent suicide attempts related to mental illness have not been addressed in the literature to date. Method: This paper is a collaborative case study between graduates (experts by experience) and facilitators of a psychosocial/psychoeducational group for people with recurrent suicide attempts. The journeys taken by the experts by experience are explored through thematic narrative analysis. Findings/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…As identified in “Normalising my life: the positive impact of work”, the participants indicated that work is extremely important to self‐esteem, pride and self‐worth, resulting in positive changes and a newfound confidence. This corroborates the work of Craik et al (2010), Arthur et al (2009) and Bergmans et al (2009).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As identified in “Normalising my life: the positive impact of work”, the participants indicated that work is extremely important to self‐esteem, pride and self‐worth, resulting in positive changes and a newfound confidence. This corroborates the work of Craik et al (2010), Arthur et al (2009) and Bergmans et al (2009).…”
Section: Discussionsupporting
confidence: 92%
“…Qualitative research carried out within this field has found that engaging in a meaningful occupation can bring a sense of achievement, it can have a positive effect on mental health and provide a sense of purpose (Craik et al , 2010; Arthur et al , 2008; Bergmans et al , 2009). However, only the study by Craik et al (2010) was carried out within a forensic setting.…”
Section: Current Researchmentioning
confidence: 99%
“…Study numbers: 1 = [62], 2 = [58], 3 = [56], 4 = [65], 5 = [61], 6 = [60], 7 = [66], 8 = [67], 9 = [55], 10 = [68], 11 = [57], 12 = [59], 13 = [63], 14 = [69], 15 = [64], 16 = [54], 17 = [28]…”
Section: Resultsmentioning
confidence: 99%
“…In occupational therapy, transition viewed from the patient/client's perspective considered, for instance the clients' perspective on the return to work (Bergmans et al, 2009;Švajger & Winding, 2009), recovery patterns (Prvu Bettger, Coster, Latham, & Keysor, 2008) and the experience of mental illness (McKay, 2010). Transition viewed from the professional perspective in this discipline focused on home-based rehabilitation (Cook et al, 2013) and school involvements (Michaels & Orentlicher, 2004).…”
Section: From Which Perspective Was Transition Seen?mentioning
confidence: 99%